Distinctive transnational city-to-city partnerships, decentralization, and local governance of China as a Global East Country. - Jili Xu; Huaikuan Liu; Gengzhi Huang (PLoS ONE, 2023)
Against the background of globalisation and state rescaling, promoting decentralisation and enhancing local governance capacity have become prioritised objectives of transnational city-to-city partnerships mainly between developed and developing countries. However, considering the critical debates on Global East's uniqueness, two questions emerge when studying the transnational partnerships of Chinese cities. (1) Are Chinese cities' partnership establishments and objectives remarkably different from the existing international body of knowledge? (2) In China, whether decentralisation and local governance are promoted by city-to-city transnational partnerships as well? To cope with the questions, this paper examines 28 Chinese world cities' partnership establishments and objectives and reaches two conclusions. (1) With the objective of economic development, Chinese cities have consistently maintained strong connections with cities in both the developed and developing countries. (2) Chinese cities' transnational partnerships do not observably promote decentralisation, and China's political decentralisation is much more unstable than its economic decentralisation. Overall, both the binary partnership establishments and the dual-track decentralisation in political and economic aspects are highly embedded in China's interstitial and transitional position as a Global East country.